Bielszy odcień inteligencji: o różnicach rasowych i etnicznych w kontekście badań nad inteligencją - Albański, Łukasz (Studia Edukacyjne, 2019)
This article addresses the issue of racial and ethnic differences in intelligence studies. Some researchers have claimed to use national IQs in studies of evolutionary theories of racial differences in intelligence. However, due to the Flynn Effect and some methodological questions, national IQs cannot be viewed solely in evolutionary and socio-economic development terms and can be considered in light of intercultural differences as well. Moreover, the meaning of race in intelligence studies is vaguely defined. It leads to considerable controversies surrounding the public understanding of race (for instance, stereotyping threat). It also creates suspicions as to the use of group differences in IQ tests to explain racial and ethnic differences in achievements.